2019
DOI: 10.1371/journal.pbio.3000161
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and effects of nucleosides in mice lacking all four adenosine receptors

Abstract: Adenosine is a constituent of many molecules of life; increased free extracellular adenosine indicates cell damage or metabolic stress. The importance of adenosine signaling in basal physiology, as opposed to adaptive responses to danger/damage situations, is unclear. We generated mice lacking all four adenosine receptors (ARs), Adora1−/−;Adora2a−/−;Adora2b−/−;Adora3−/− (quad knockout [QKO]), to enable investigation of the AR dependence of physiologic processes, focusing on body temperature. The QKO mice demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 86 publications
1
48
0
Order By: Relevance
“…Interestingly, using the PET radioligand, [ 11 C]TMSX, which binds specifically to the A2aAR, lean men were found to have reduced brown adipose tissue radioligand binding (a marker of A2aAR receptor density) following cold exposure [ 84 ]. However, in mice lacking all four ARs, termed quadruple knockout mice (QKO), body temperature did not differ from WT mice [ 85 ], suggesting that ARs are not necessary for baseline body temperature or that the four adenosine receptors may have reciprocal and opposing effects on body temperature such that deletion of one adenosine receptor is balanced by the deletion of a different adenosine receptor. Regardless, the role of the A2aAR in brown adipose tissue appears to be clinically relevant and may lead to future therapeutic efforts.…”
Section: Adenosine Receptors In Glucose Homeostasis and Obesitymentioning
confidence: 99%
“…Interestingly, using the PET radioligand, [ 11 C]TMSX, which binds specifically to the A2aAR, lean men were found to have reduced brown adipose tissue radioligand binding (a marker of A2aAR receptor density) following cold exposure [ 84 ]. However, in mice lacking all four ARs, termed quadruple knockout mice (QKO), body temperature did not differ from WT mice [ 85 ], suggesting that ARs are not necessary for baseline body temperature or that the four adenosine receptors may have reciprocal and opposing effects on body temperature such that deletion of one adenosine receptor is balanced by the deletion of a different adenosine receptor. Regardless, the role of the A2aAR in brown adipose tissue appears to be clinically relevant and may lead to future therapeutic efforts.…”
Section: Adenosine Receptors In Glucose Homeostasis and Obesitymentioning
confidence: 99%
“…It is present in all cells containing glia and neurons, initiates its biological process by four G-protein coupled receptors (GPCRs), namely, the A1, A2A,…A2BAR [ 43 , 44 ]. It has a role in regulating and integrating neuronal excitability, affecting many essential brain activities like sleep, memory, and neural plasticity [ 45 , 46 , 47 ]. Much research has analyzed adenosine effects via its receptors A1 and A2A in AD [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…The four AR subtypes (A 1 , A 2A , A 2B , and A 3 ; Figure 1) are important in the body's adaptation to stress [1,3], often in the context of increasing local blood flow by vasodilation. However, a knockout (KO) mouse line lacking all four ARs displayed no differences in growth, fertility, metabolism, and thermal regulation, although long-term survival was diminished [2]. This suggested that ARs have a more pronounced role to regulate allostasis, i.e., to restore the stability of an organism in response to challenges or stresses, than homeostasis, which maintains unperturbed physiological parameters.…”
Section: Endogenous Adenosinementioning
confidence: 99%
“…Drugs can affect adenosine signaling in multiple ways. They can act directly as ligands for one or more of the four G protein-coupled receptors (GPCRs) for adenosine [1][2][3]. Alternatively, they can stimulate or inhibit pathways of adenosine generation, degradation, or clearance [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%